Digital Platforms and the Financial Feasibility of Halal Frozen Food Marketing: A Feasibility Assessment - Gandhi, Prima; Yulianti, Alma Sophia; Andri, Kuntoro Boga; Dewi, Sari Putri; Purbawan, Ketut Wira (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2024)
The Indonesian government issued a national policy of large-scale social restrictions in 2020 to 2021. At the same time, there was an increase in internet users in Indonesia which led to an increase in the use of the Tiktok mobile application. Both incidents made halal frozen food producers in Bogor market their products using mobile applications. Until now, there has been no research that calculates the financial feasibility of marketing halal frozen food using mobile applications. This study aims to determine the financial feasibility of marketing halal frozen food produced by PT XYZ using the TikTok mobile application. The financial feasibility analysis in this study uses a quantitative method by calculating income and assessing investment feasibility based on cash flow in the form of an R/C ratio. Researchers conducted observations and interviews as data collection techniques. The research location and respondents were selected purposively. The types of research data used are primary data and secondary data. Based on the results of the study, the net profit received by the company increased by IDR 118,714,448 with an R/C ratio of 2.52, meaning that every cost incurred of IDR 1 will get an income of IDR 2.52. From the explanation above, the results of this study prove that marketing of halal frozen food at PT XYZ Bogor using mobile applications is feasible and profitable. The implication of this study is to recommend halal frozen food producers in countries with increasing internet usage trends to market using mobile applications in order to obtain maximum profit.